O corpo desejante como sustentação do discurso da revista Capricho Week - Garbossa, Maria Roseli Castilho (2019)
The present research investigates the discourse of the magazine Capricho Week about the body in relation to the adolescent female audience, seeking to observe the meaning effects of body that are legitimated in the media while others are erased. To think about the question of the meanings of body discursivized in the magazine requires to remember that it is not of the empirical body we are talking about, but of the body that is interpellated, of the symbolic body, of the body that produces meaning effects, where ideology works, whose specific materiality is the discourse. In this direction, we start from some questions: What are and how are produced the discourses about the female adolescent body? From which discursive and ideological formations do they emerge? How is the body built from what is said about it and how it should be? This thesis is founded on the search for answers to these questions. For this purpose, we mobilize the theoretical and methodological framework of French Discourse Analysis, to which the meaning effects are produced by social positions and the subjects act according to these positions, situated in one and not in another discursive formation according to their conditions of production. As for the corpus of this research, it is composed of discursive sequences of the digital magazine Capricho Week, from the years 2015 to 2017. Considering that the meaning effects about the body are produced under given conditions of production that are constituted by historically constructed relations of meaning by the subjects, we add to our corpus discursive sequences taken from the magazine Capricho, the printed version, from 1970 to 2015, due to its importance for the understanding of the discursive processes in the constitution of the body, the meanings and the subjects. Needs are imposed and stimulated on the adolescent at every moment: the globalized world of the market revolves in a circular way, and it is not possible to reach a final stage. When the adolescent finally succeeds in meeting a need, others arise: the cycle of satisfaction is not complete. In this movement, the media takes advantage to spread the model of body socially admired and accepted and, from this, stimulates consumerism as an attempt to achieve completeness for the adolescent, who, driven by the constitutive lack, and interpellated by the discursive formation of advertising consumerism, believes that one day she will reach the idealized model of body.